2012
DOI: 10.3168/jds.2012-5405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling heat-stressed dairy cows during the dry period on insulin response

Abstract: Heat stress (HT) during the dry period affects hepatic gene expression and adipose tissue mobilization during the transition period. In addition, it is postulated that HT may alter insulin action on peripheral tissues. Our objective was to evaluate the effect of cooling heat-stressed cows during the dry period on insulin effects on peripheral tissues during the transition period. Cows were dried off 46 d before expected calving and assigned to 1 of 2 treatments: HT (n = 16) or cooling (CL, n = 16). During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 32 publications
(54 reference statements)
9
81
2
Order By: Relevance
“…It is known that heat stress plays an important role in depressing plasma insulin concentration of dairy cows (Itoh, Obara, Rose, & Fuse, ; Tao et al., ), which is in agreement with the current study, that high SD‐stressed animals had lower plasma insulin content. In the current study, plasma glucagon contents did not differ between 75SD‐ and 100SD‐cows.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is known that heat stress plays an important role in depressing plasma insulin concentration of dairy cows (Itoh, Obara, Rose, & Fuse, ; Tao et al., ), which is in agreement with the current study, that high SD‐stressed animals had lower plasma insulin content. In the current study, plasma glucagon contents did not differ between 75SD‐ and 100SD‐cows.…”
Section: Discussionsupporting
confidence: 93%
“…In mid-lactating dairy cows, higher plasma cortisol was found when they were in a greater SD than that of lower SD condition (Pence et al, 2005). However, in the current study, plasma cortisol concentrations did not differ between the cows of the two treat- It is known that heat stress plays an important role in depressing plasma insulin concentration of dairy cows (Itoh, Obara, Rose, & Fuse, 1998;Tao et al, 2012), which is in agreement with the current study, that high SD-stressed animals had lower plasma insulin content. In the current study, plasma glucagon contents did not differ between 75SD-and 100SD-cows.…”
Section: Discussionsupporting
confidence: 92%
“…Late gestation heat stress has been reported to either shorten or not affect gestation length in human and farm animals (Collier et al, 1982; Porter et al, 1999; Tao et al, 2012; Williams et al, 2013). We found no effect of gestational heat stress on gestation length in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there is no literature data related to fi eld studies on insulin response to glucose challenge in cows continuously exposed to heat stress during the early lactation and midlactation periods. Recently, Tao et al, (2012) [11] presented results of insulin response to glucose challenge in dry cows exposed to heat stress and concluded that insulin response to IVGTT varies according to the phase of productive-reproductive cycle. Therefore, the results related to IVGTT in heat-stressed cows at days 30 and 60 of lactation can not be directly comparable with others.…”
Section: Graph 2 Milking Yields During the Summer And Spring Periodmentioning
confidence: 99%
“…It is still an open question if the realignment of metabolism in conditions of heat stress is any different during the early stages of lactation when cows usually are in a stage of negative energy balance. Recently, Tao et al (2012) [11] emphasized the importance of studying the insulin response of heat-stressed cows in all phases of productive-reproductive cycle including the dry period, too.…”
Section: Introductionmentioning
confidence: 99%